The Role of Meaningful Work, Work Engagement, and Strength Use in Enhancing Teachers’ Job Performance: A Case of Indonesian Teachers - Anggraheni Maria Dewinta; Sudibjo Niko; Harsanti HG Retno (Open Education Studies)
The literature reveals a gap in the understanding of the impact of meaningful work (MW) and strength use (SU) on teachers’ job performance (JP), which has not been widely studied. Additionally, the roles of SU and work engagement (WE) as mediating variables affecting teachers’ perceptions of MW in JP are less explored. This study addresses these gaps by determining the effect of MW on teachers’ JP and the roles of WE and SU in mediating the effect of MW on JP, which is evident. A quantitative approach was employed using a cross-sectional study design, applying partial least squares structural equation modeling. Data were obtained through a survey of 392 private high school teachers in Jakarta, Indonesia, using a convenience sampling method. The key findings of this study indicate that while MW has the smallest direct effect on JP, it is the construct with the highest importance and performance. WE and SU successfully mediate the effect of MW on JP, significantly enhancing the influence of MW on JP. Consequently, school leaders are advised to enhance teachers’ WE and SU by adjusting teaching loads according to educational backgrounds, providing incentives for additional work, supporting competency improvement, and encouraging knowledge sharing among teachers.